2014
DOI: 10.2478/cpe-2014-0034
|View full text |Cite
|
Sign up to set email alerts
|

Methods of Thermal Calculations for a Condensing Waste-Heat Exchanger

Abstract: The paper presents the algorithms for a flue gas/water waste-heat exchanger with and without condensation of water vapour contained in flue gas with experimental validation of theoretical results. The algorithms were used for calculations of the area of a heat exchanger using waste heat from a pulverised brown coal fired steam boiler operating in a power unit with a capacity of 900 MW e . In calculation of the condensing part, the calculation results obtained with two algorithms were compared (Colburn-Hobler a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The model of associated processes i.e. degasing, gasification and combustion of solid waste is an objectoriented and reactive (event driven) model [16]. It is the implementation of a mathematical model in a source code of a high-level language (RAD) environment, using design techniques and Component-oriented analysis CCA (Common Component Architecture).…”
Section: Component Oriented Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The model of associated processes i.e. degasing, gasification and combustion of solid waste is an objectoriented and reactive (event driven) model [16]. It is the implementation of a mathematical model in a source code of a high-level language (RAD) environment, using design techniques and Component-oriented analysis CCA (Common Component Architecture).…”
Section: Component Oriented Modelmentioning
confidence: 99%
“…The reducing gases from the central reactor and the degassing chamber (model description-as in units 1, 2, 3) -UPPER REACTOR. Due to complexity of the actual process of high -temperature fuel combustion, a number of assumptions was made, which allow to precisely define the model and ignore details of no significance for simulation calculations (e.g, an assumption that the model parameters are subject to additivity) [16,18].…”
Section: Mathematical Model Of Ther-mal Waste Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the aspect of TSS design, the existing research mainly focuses on the thermal calculation of parts of the TSS, such as separate heat exchangers, heat storage modules, etc. Raczka et al [13] and Fujii et al [14] introduced the design and calculation method of flue gas/waste water-heat exchanger and indirect heat exchanger, respectively. Du et al [15] also reported a design method for heat storage units.…”
Section: Introductionmentioning
confidence: 99%
“…The function purpose of the heat exchanger installed is to increase the heat flux recovered through condensation of water vapour contained in the flue gas. Mathematical modelling and designing such a heat exchanger is a difficult task due to the complex model describing the heat transfer in the presence of inert gas, a concentration of water vapour, the effect of condensation, and a limitation resulting from a large heat flux that affects the overall dimensions of the exchanger (Chaojun et al, 2012;Chaojun et al, 2014;Dexin et al, 2012;Rączka et. al., 2014;Szulc et al, 2012;Szulc et al, 2013;Xiaojun et al, 2011).…”
Section: Introductionmentioning
confidence: 99%